2014
DOI: 10.1109/tr.2014.2315917
|View full text |Cite
|
Sign up to set email alerts
|

Component Redundancy Versus System Redundancy in Different Stochastic Orderings

Abstract: Stochastic orders are useful to compare the lifetimes of two systems. We discuss both active redundancy as well as standby redundancy. We show that redundancy at the component level is superior to that at the system level with respect to different stochastic orders, for different types of systems.Index Terms-Coherent system, -out-of-system, reliability, stochastic orders. ACRONYMSAND ABBREVIATIONS st usual stochastic sp stochastic precedence hr hazard rate rhr reversed hazard rate lr likelihood ratio up shifte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Barlow and Proschan [4] showed that the allocation of active redundancy at the component level (of a coherent system) is superior to that at the system level with respect to the usual stochastic order. Later, many other researchers studied this problem in different directions (see [8], [11], [21], [38], [40], [56], [57], and the references therein). However, to the best of our knowledge, this problem using ageing faster orders has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Barlow and Proschan [4] showed that the allocation of active redundancy at the component level (of a coherent system) is superior to that at the system level with respect to the usual stochastic order. Later, many other researchers studied this problem in different directions (see [8], [11], [21], [38], [40], [56], [57], and the references therein). However, to the best of our knowledge, this problem using ageing faster orders has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The general problem of where to allocate an active or standby redundant component has been studied along the 90's, as can be seen in related works . More recently, additional results have been provided by other works …”
Section: Introductionmentioning
confidence: 99%
“…For the matching case, the BP principle was sequentially enhanced to the (reversed) hazard rate, likelihood ratio, and some shifted stochastic orderings. See, for example, and . However, there is less work for the non‐matching case because of the complexity of distribution theory.…”
Section: Introductionmentioning
confidence: 99%